Kinerja Ekonomi Industri Kecil Agro yang Telah Bertahan Lintas Generasi di Priangan Timur - Charina, Anne; Kusumo, Rani Andriani Budi; Wibawa, Gema (Universitas Galuh, 2024)
This study explores how the economic performance of agricultural small industries has survived for three generations in rural East Priangan. This study is important because of the high failure rate of small industries in Indonesia. This research uses a qualitative approach. Data was obtained through semi-structured interviews, FGDs, and secondary data from companies. Qualitative data was analyzed using the principles of Thematic Analysis assisted by N-Vivo 12 software. The results of the research show that the economic performance of agricultural small industries that have survived for three generations in rural areas is still in a poor status. The practical implications of these findings are that: Profitability, level of innovation, level of competition, are the most sensitive factors and need to be considered in improving economic performance. This paper highlights that long-lived agricultural small industries do not necessarily have good economic performance. Many of these small industries survive based on commitment, maintaining their family's good name and conventional orientation.